How We Are Governed : Investigations of Communication, Media and Democracy. - Dearman, Philip (Cambridge Scholars Publishing, 2014)
How We Are Governed explores interdisciplinary relations between communication and politics. It brings together diverse perspectives from the field of Communication and Media Studies, focusing on formal arenas of politics and public policy as well as politics in the broad sense of an informal negotiation of social relations of power between people. The book deals with questions about governing across many different domains, paying particular attention to communicative practices and technolo ...